Aberrant WNT/CTNNB1 Signaling as a Therapeutic Target in Human Breast Cancer: Weighing the Evidence - van Schie, Emma H.; van Amerongen, Renée (Frontiers in Cell and Developmental Biology, 2020)
WNT signaling is crucial for tissue morphogenesis in all multicellular animals. It also plays a critical role after embryonic development, by controlling tissue maintenance and regeneration in the adult. Disbalanced WNT pathway activity can thus cause congenital disorders as well as disease later in life. In the adult human body, WNT/CTNNB1 responsive stem cells are responsible for tissue homeostasis in various organs and hyperactive WNT/CTNNB1 signaling is observed in many different cancers. The first link between WNT signaling and breast cancer was established almost forty years ago, when the founding member of the mammalian Wnt gene family, Wnt1, was identified as a proto-oncogene capable of driving mammary tumor formation in mice. Since this discovery, aberrant WNT signaling has also been implicated in human breast cancer. However, many questions remain. First, the overall extent and precise type of (epi)genetic changes affecting the WNT pathway in different breast cancer subtypes are still unknown. Second, which underlying molecular and cell biological mechanisms are disrupted as a result awaits further scrutiny. Here, we discuss recent developments and current research gaps in this area. We specifically highlight what is known and unknown about the role of WNT signaling in human breast development and normal physiology and discuss to what extent WNT/CTNNB1 signaling should be the sole focus of attention when it comes to the involvement of the WNT pathway in human breast cancer. Finally, we survey the current status of targeted therapeutics that are aimed at interfering with the WNT pathway in breast cancer patients.